2012
DOI: 10.1002/smll.201201870
|View full text |Cite
|
Sign up to set email alerts
|

Shuttle‐Mediated Nanoparticle Delivery to the Blood–Brain Barrier

Abstract: Many therapeutic drugs are excluded from entering the brain due to their lack of transport through the blood-brain barrier (BBB). The development of new strategies for enhancing drug delivery to the brain is of great importance in diagnostics and therapeutics of central nervous diseases. To overcome this problem, a viral fusion peptide (gH625) derived from the glycoprotein gH of Herpes simplex virus type 1 is developed, which possesses several advantages including high cell translocation potency, absence of to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
84
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 88 publications
(92 citation statements)
references
References 44 publications
8
84
0
Order By: Relevance
“…31,32 We have previously demonstrated that gH625, a 19-residue peptide, is a membrane-perturbing domain 13 that interacts with model membranes, contributing to their merging 13 and is able to traverse the membrane bilayer and transport a cargo (quantum dots, liposomes, and dendrimers) 16,18,20 into the cytoplasm and across an in vitro model of the BBB. 19 Uptake studies suggested a nonactive translocation mechanism in crossing the lipid bilayer, which may vary depending on the cargo. 15 Penetration by gH625 occurs in a rapid, concentration-dependent fashion that appears to be independent of receptors and transporters and instead is thought to target the lipid bilayer component of the cell membrane.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…31,32 We have previously demonstrated that gH625, a 19-residue peptide, is a membrane-perturbing domain 13 that interacts with model membranes, contributing to their merging 13 and is able to traverse the membrane bilayer and transport a cargo (quantum dots, liposomes, and dendrimers) 16,18,20 into the cytoplasm and across an in vitro model of the BBB. 19 Uptake studies suggested a nonactive translocation mechanism in crossing the lipid bilayer, which may vary depending on the cargo. 15 Penetration by gH625 occurs in a rapid, concentration-dependent fashion that appears to be independent of receptors and transporters and instead is thought to target the lipid bilayer component of the cell membrane.…”
Section: Discussionmentioning
confidence: 99%
“…15 Further, gH625 has been used extensively for vector-mediated strategies that enable passage of a large variety of small molecules as well as proteins across cell membranes in vitro. [16][17][18][19][20] Conjugation of gH625 to the surface of nanoparticles also enhances their transport across the BBB, as previously demonstrated in an in vitro model of the BBB. 19 Whether or not multifunctional nanodevices, designed and tested in vitro, work properly in vivo in a mammalian host is still not fully understood.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…In addition, gH625 has been used to efficiently deliver quantum dots in cells, that do not significantly traverse the membrane bilayer on their own; 18 liposomes; 17 dendrimers; 1 or nanoparticles through the blood-brain barrier. 2 Therefore, gH625 can be considered a promising tool to efficiently perform intracellular delivery and may represent an alternative strategy to the use of the well characterized positively charged TAT peptide.…”
Section: Discussionmentioning
confidence: 99%
“…1,2,17,18 In particular, we recently reported the ability of gH625 peptide to transport quantum dots inside the cytoplasm in an efficient way and only partially involving endocytic pathways; 18 moreover, we reported its ability to enhance intracellular penetration of liposomes functionalized with the peptide on the external leaflet, 17 nanoparticles, 2 and dendrimers. 19 Compared with the TAT peptide, which mainly exploits the endocytic pathway, the viral membranotropic peptide gH625 crosses membrane bilayers mainly through a translocation mechanism.…”
Section: Introductionmentioning
confidence: 91%